Optimization of cyclone efficiency for separation of fibre and shell from palm kernel - Khairul Azlan, Ismail (2012)
In separation of shell and fibre from kernel seed, palm oil mill normally employed cyclone system.A cyclone collection consists of cylindrical shell,conical base,dust hopper,and an inlet where the dust laden enters tangentially.Under the influence of the centrifugal force generated by the spinning gas,the solid particles are thrown to the wall of the cyclone as the gas spirals upward at the inside of the cone. The particles slide down to the wall of the cone and into the hopper.The operating or separating efficiency of a cyclone depends on the magnitude of the centrifugal force exerted on the particles.The greater the centrifugal force, the greater the separating efficiency.The magnitude of the centrifugal force depends on particle mass,gas velocity within the cyclone and cyclone diameter.For a practical test to increase the cyclone efficiency for kernel recovery,gas velocity can be manipulated to achieve highest separation efficiency instead of modifying the cyclone design.In experimental,the total load entering the system and various inlet velocity of the cyclone is measured.The kernel and shell production will be measured 1 hour after change is made.Data obtained was analyzed to determine the inlet air velocity for the maximum separation efficiency indicates by the highest peak of kernel production in graph.The result compared 2 loads entering the system and the different load give different best air velocity.Increase the load will increase the best inlet air flow.Higher air velocity will reduce the separation efficiency.